The pharmacologenetics of lopinavir in a cohort of black African HIV/AIDS patients - Mpeta, Bafokeng (Division of Human Genetics, 2015)
The Sub-Saharan African region remains the most severely affected by the HIV/AIDS epidemic. At the end of 2011, The Joint United Nations Programme on HIV/AIDS (UNAIDS) estimated that about 5% of adults were living with the HIV in this region, accounting for 69% of the global HIV prevalence. Efforts to curb the epidemic are focused on managing HIV through prevention strategies, such as advocating the use of condoms or pre-exposure or post-exposure prophylactic treatment, and prolonging life through the use of antiretroviral (ARV) therapy. Drugs used in ARV therapy target different major steps of the HIV reproductive cycle. These are nucleoside and non-nucleoside reverse transcriptase inhibitors (NRTIs/NNRTIs); fusion/entry inhibitors; integrase inhibitors; and protease inhibitors (PIs). In South Africa PIs, specifically lopinavir (LPV) boosted with another PI, ritonavir (RTV) are used in second-line ARV regimens along with a backbone of 2 NRTIs. The use of ARVs is not without issues - patients often experience side-effects to the drugs such as nausea, diarrhoea, and lipodystrophy with LPV use, which may influence their adherence to treatment and eventually lead to treatment failure. Inter-individual variability exists in patients' response to treatment despite the standard dose of 400 mg/100 mg (LPV/RTV) that is given and this may be due to differences in transport or metabolism of the drug in the liver. High plasma drug levels (associated with side-effects or toxicity) may be a result of poor metabolism or conversely, low plasma drug levels (associated with failure to suppress the virus) may be a result of extensive metabolism of the drug. Proteins involved in the disposition of LPV include the drug metabolising enzymes, CYP3A4 and CYP3A5; the hepatic uptake transporter, OATP1B1; and the efflux transporter, MRP2. Variation in the genes encoding these proteins may influence their functioning and hence LPV disposition. The aim of the study was to identify significant single nucleotide polymorphisms (SNPs) in each gene; to genotype a cohort of HIV-infected patients from Malawi and South Africa to identify the frequency of those variants; and to correlate genotypes with LPV plasma levels and other clinical parameters.